2020
DOI: 10.1002/acm2.12948
|View full text |Cite
|
Sign up to set email alerts
|

In search of a one plan solution for VMAT post‐mastectomy chest wall irradiation

Abstract: This study was designed to evaluate skin dose in both VMAT and tangent treatment deliveries for the purpose of identifying suitable bolus use protocols that should produce similar superficial doses. Methods: Phantom measurements were used to investigate skin dose in chest wall radiotherapy with and without bolus for 3D and rotational treatment techniques. Optically stimulated luminescence dosimeters (OSLDs) with and without housing and EBT3 film were used. Superflab (3, 5, and 10 mm) and brass mesh were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
3
10
1
Order By: Relevance
“…VMAT planning resulted in a decreased dose on the lateral aspect of the phantom consistent with an increased curvature of the surface. In contrast to Monajemi et al who reported negligible variability for the central 8 cm of the treatment area, 14 the data in this manuscript are reported for approximately 20 cm along the chest wall and shows significant variability. We believe that our measurements demonstrate similar profiles over smaller sections of the chest wall, but acknowledge that deviations may be a result of the planning process.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…VMAT planning resulted in a decreased dose on the lateral aspect of the phantom consistent with an increased curvature of the surface. In contrast to Monajemi et al who reported negligible variability for the central 8 cm of the treatment area, 14 the data in this manuscript are reported for approximately 20 cm along the chest wall and shows significant variability. We believe that our measurements demonstrate similar profiles over smaller sections of the chest wall, but acknowledge that deviations may be a result of the planning process.…”
Section: Discussioncontrasting
confidence: 99%
“…Monajemi et al reported the dose enhancement for different p-bolus regimens using pseudo-flash VMAT to 83% for BMB and 96% for 3 mm TEB using a custom phantom based on a specific patient. 14 This work included the pseudo-flash VMAT component but lacks a variety of field arrangements to confirm the robust process of this planning strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The RD ≥Grade 2 (38.7%) was lower than that reported in other studies 38–40 . As in previous reports, the frequency of ≥Grade 2 RD was 40%–90% for patients treated with a conventional technique, 35 and 42% for patients treated with IMRT 39 . The results of Arsenault's study (38%) are similar to our findings 40 .…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the effect of the air gap on the dose distribution of the OAR and targets, the thickness of the bolus will also change the dose to the skin 35‒37 . Monajemi et al showed that average skin doses in postmastectomy VMAT treatments with a 3, 5, and 10 mm bolus were 0.96, 1.03, and 1.04, respectively 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study is to investigate impact of bolus thickness on robustness of VMAT against setup errors in PMRT of left-sided breast cancer. Dose distribution in the targets and the OARs in VMAT with different bolus thicknesses are also evaluated since most of the published reports only focused on skin dose [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%